Home- and Community-Based Waivers for Children With Autism: Effects on Service Use and Costs - Cidav, Zuleyha (Intellect Dev Disabil, 2014)
We examined (a) the associations between Medicaid home and community-based waiver participation and service use and expenditures among children with ASD; and (b) how states’ waiver spending moderates these effects. We used 2005 Medicaid claims to identify a sample of children with autism spectrum disorder (ASD). We selected two comparison groups who had no waiver participation: (a) children who were eligible for Medicaid through disability (disability group), and (b) children who had at least one inpatient/long-term care (IP/LT) episode (IP/LT group). Waiver participants were less likely to use IP/LT services and had lower associated expenditures than the disability group. As states’ waiver spending increased, waiver participants became increasingly less likely to use IP/LT services. Waiver participants had more outpatient visits and associated expenditures; this difference increased as state waiver spending increased. Compared with the IP/LT group, waiver participants had lower IP/LT expenditures, more outpatient visits, and associated expenditures. Higher state waiver generosity increased this effect on outpatient visits and expenditures.